Dampak Pandemi Covid-19 terhadap Perekonomian Indonesia - Ramadhani, Yesa Cahayaning (Fakultas Ekonomi Universitas Samudra, 2023)
The purpose of this research is to analyze the impact of the Indonesian economy during the Covid-19 pandemic. The population in this study is the economy in Indonesia caused by the Covid-19 pandemic. The determination of the sample was carried out using a purposive sampling technique, based on certain criteria in 2019–2020. The data source used is secondary data obtained in the form of observations of the economy in Indonesia which has been affected by the Covid-19 pandemic (online). Testing the research hypothesis using the SEM analysis method (structural equation model). The first results obtained show that inflation and the unemployment rate have proven to have a significant positive effect on the Indonesian economy; while the Covid-19 pandemic has had a positive but unsignificant effect on the Indonesian economy. The second result found that inflation proved to have a positive but unsignificant effect on national investment; on the other hand, the unemployment rate and the Covid-19 pandemic proved to have a positive and significant effect on national investment.